Medical Subject Headings and medical terminology: an analysis of terminology used in hospital charts. - Masarie, F E (1987)
Terminology used by health professionals in everyday written discourse was compared with terminology in a standardized medical vocabulary, the Medical Subject Headings (MeSH). Fifty written hospital charts were selected at random and analyzed by a computer program that identified MeSH terms in the charts. The charts were analyzed against two related MeSH vocabularies--one containing MeSH terms and one containing both MeSH terms and backwards cross-reference terms. When small words such as articles and prepositions were disregarded, approximately 50% of the words in a medical chart were found to be MeSH-related terminology. In addition, about 40% of MeSH-related words in the charts were either MeSH terms or backwards cross-reference terms.